Fluctuating water levels control water chemistry and metabolism of a charophyte‐dominated pond. (12th April 2013) - Christensen, Jesper P. A.; Sand‐Jensen, Kaj; Staehr, Peter A.
Summary To investigate seasonal variability and importance of environmental drivers of ecosystem metabolism in a shallow pond characterised by low and fluctuating water depth, clear water and shortage of nutrients, we measured primary production and respiration during May–September and examined their relationships to environmental parameters (light, temperature and pH). Using a combination of free water measurements of O2, pH, temperature and conductivity, in situ mesocosm and laboratory bottle experiments, we documented extreme daily variations in environmental variables (e.g. 0–700 mmol O2 m−3, pH 7.5–9.5, 18–32 °C) and high and variable areal rates of gross primary production (GPP, 30–316 mmol O2 m−2 day−1) and community respiration (R, 26–318 mmol O2 m−2 day−1). These rates of benthic charophytes under oligotrophic conditions are comparable to those obtained by pelagic phytoplankton communities under highly eutrophic conditions. By using sediment resources, benthic charophytes can achieve high biomasses and high metabolic rates. Pond metabolism reflected the physiology of the dominant charophyte, with light‐saturated photosynthesis occurring during 55% of the light hours. Experiments and photosynthetic models showed inorganic carbon limitation of GPP at pHs above 9.5 during mid‐summer periods of low water levels, while R was strongly influenced by temperature. According to open water measurements of O2, the pond was net autotrophic (mean NEP = 12 ± 13 (SD) mmol O2 m−2 day−1) but net heterotrophic when based on dissolved inorganic carbon (DIC) dynamics (10 ± 29 mmol CO2 m−2 day−1), suggesting that the significant input of DIC in inflowing water from the surrounding limestone soils mimics elevated respiration.